تحليل إدارة المخاطر التشغيلية في المصرف التجاري السوري خلال الفترة2004 حتى 2011 - العشعوش أيمن; غضبان عبادة (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يهدف هذا البحث إلى التعريف بماهية المخاطر التشغيلية وأنواعها والممارسات السليمة لإدارة ورقابة تلك المخاطر في المصرف التجاري السوري وفق قرارات مجلس النقد والتسليف. حيث أن المنهج الصحيح لإدارة المخاطر التشغيلية الذي يختاره أي مصرف يعتمد على مجموعة من العوامل يدخل ضمنها حجم المصرف وتطوره وطبيعة نشاطه ومستوى تعقيده. وتتجلى أهمية البحث من خلال تسليط الضوء على أهم الأساليب والمؤشرات المستخدمة لقياس المخاطر التشغيلية وحساب المتطلب الرأسمالي لمقابلة تلك المخاطر، ومعرفة مدى التزام المصرف التجاري السوري بتطبيق قرارات مجلس النقد والتسليف لإدارة المخاطر التشغيلية. ومن أهم النتائج التي توصلنا إليها تقديم المصرف البيئة المناسبة لإدارة المخاطر التشغيلية ، إلا أن هناك ضعف في قدرة المصرف على المراقبة والتخفيف من المخاطر التشغيلية. This research aims to introduce the essence and types of the operational risks and good practices to manage and control these risks in the Commercial Bank of Syria in accordance with the Monetary and Credit Council resolutions. Since the correct approach to the management of operational risks chosen by any bank depends on a variety of factors including the size enters the bank and its evolution and the nature of its activity and the level of complexity. The importance of research by highlighting the most important methods and indicators used to measure and calculate the operational risk capital requirement to meet those risks, and see how Commercial Bank of Syria’s commitment to implement decisions of the Monetary and Credit Council for the management of operational risks. The most important of our findings provide an appropriate environment for the bank’s operational risk management ,but there are weaknesses in the bank’s ability to control and mitigate the operational risk.